Radical Complexes of Nickel(II)/Copper(II) and Redox Non‐innocent MB‐DIPY Ligands: Unusual Stability and Strong Near‐Infrared Absorption at λmax ∼1300 nm. Issue 41 (24th June 2022) - Zatsikha, Yuriy V.; Shamova, Liliya I.; Shepit, Michael; Berry, Steven M.; Thomas, Fabrice; Herbert, David E.; van Lierop, Johan; Nemykin, Victor N.
Abstract: The preparation of radicals with intense and redox‐switchable absorption beyond 1000 nm is a long‐standing challenge in the chemistry of functional dyes. Here we report the preparation of a series of unprecedented stable neutral nickel(II) and copper(II) complexes of "Manitoba dipyrromethenes" (MB‐DIPYs) in which the organic chromophore is present in the radical‐anion state. The new stable radicals have an intense absorption at λ max ∼1300 nm and can be either oxidized to regular [M II (MB‐DIPY)] + (M=Cu or Ni) or reduced to [M II (MB‐DIPY)] − compounds. The radical nature of the stable [M II (MB‐DIPY)] complexes was confirmed by EPR spectroscopy with additional insight into their electronic structure obtained by UV‐Vis spectroscopy, electro‐ and spectroelectrochemistry, magnetic measurements, and X‐ray crystallography. The electronic structures and spectroscopic properties of the radical‐based chromophores were also probed by density functional theory (DFT) and time‐dependent DFT (TDDFT) calculations. These nickel(II) and copper(II) complexes represent the first stable radical compounds with a MB‐DIPY ligand. Abstract : MB‐DIPY‐based stable radicals with redox‐switchable absorption beyond 1000 nm have been prepared and characterized by spectroscopic and theoretical methods. Stable radical complexes can be either oxidized to regular [M II (MB‐DIPY)] + (M=Cu or Ni) or reduced to [M II (MB‐DIPY)] − compounds within an ∼400 mV electrochemical window.